Menstrual cycle: The importance of both the phases and the transitions between phases on training and performance - Bruinvels, G.; Hackney, A. C.; Pedlar, C. R. (Sports Medicine, 2022)
The authors present opinions based on their applied experiences of working with female athletes in combination with the existing evidence-based literature. Most of the existing menstrual cycle research focuses on a few steady-state time points within the pre-defined menstrual cycle phases, yet this disregards the day-to-day hormonal changes that women have to accommodate to perform optimally and consistently. The traditional research models are inadequate for studying symptoms and symptom management, and ultimately for supporting athletes to perform well throughout the entirety of their cycle. As such, the monitoring of the day-to-day variation, particularly during the transitions between menstrual cycle phases appears to be an important "overlooked" consideration. This is particularly pertinent considering the known intra-individual and inter-individual variation in menstrual cycle characteristics. Anecdotal and research evidence supports the idea that athletes can use non-pharmacological solutions to mitigate negative menstrual cycle symptoms and do not need to "grit their teeth and roll with it". However, further research (including case studies) is needed in this important research area. Such knowledge should be and needs to be widespread amongst practitioners and athletes as they should not have to figure this out alone. As such, researchers and practitioners need to put more work into understanding symptom aetiology, symptom clusters and their relationship with hormonal changes, menstrual cycle phases and transitions, with potential for a profound impact on individual athlete health and well-being. In so doing, those working with female athletes need to continue building on the recent progress made in educating athletes and practitioners; for example, normalising the discussion of and about the menstrual cycle and all of its implications.